Debanked: The economic and social consequences of anti-money laundering regulation - Jamie Whyte (Institute of Economic Affairs (IEA), 2024)
Debanking became a news story in 2023 when Nigel Farage alleged that Coutts had closed his account because its executives disapproved of his political opinions. A study by the Financial Conduct Authority (FCA) revealed that such ideologically motivated account closures are vanishingly rare. Nevertheless, debanking is a problem in the UK. In 2021/22, UK banks closed 343,000 accounts. In about half of those cases, the reason was that the bank could not satisfy itself that the customer was not involved in money laundering or other financial crimes. The penalties for failing to comply with the government's anti-money laundering (AML) regulations can run into hundreds of millions or even billions of pounds. Certain kinds of customers present a relatively high prima facie risk of being involved in money laundering. But the cost of discovering whether they really are criminals would exceed the value of their business. So, banks close their accounts - even though most of those people are innocent. Other customers are also harmed. Complying with AML regulations costs UK banks 34 billion a year, twice what is spent on policing all other crimes put together. This cost is ultimately borne by bank customers. There is no evidence that AML regulations reduce crime, and the governments that impose them have not even tried to show that they do. With no evidence of benefits and the costs known to be massive, the AML regulations should be scaled back, for example by going back to the pre-2017 regulatory regime, if not further. That is unlikely to happen given politicians' enthusiasm for regulation and reluctance to admit error. In that case they should compensate banks for the compliance cost. This would remove the injustice of forcing bank customers to bear the cost of fighting crime. And it would make the extraordinary cost of AML regulations politically visible.
Keywords: 330; Money laundering; bank account; regulation; compliance costs; Great Britain; Geldwäsche; Bankkonto; Regulierung; Befolgungskosten; Großbritannien